Ḥaqīqat-i Jāpān - Fa̤zlī, Shaiḵẖ Muḥammad Badrulislām (Silsilah-yi ma̤tbūʻāt-i Anjuman Taraqqī-yi Urdū, Hind, 1934)
An account of the tour in Japan, its history, language, art, religion, system of education, social life, etc.